Nutritional quality evaluation of Whitemouth croaker (Micropogonias furnieri) protein isolate - Cortez-Vega, William Renzo; Freitas, Irene Rodrigues [UNESP]; Pizato, Sandriane; Prentice, Carlos (Emerald, 2014)
Purpose: The purpose of this study was to isolate Whitemouth croaker protein by alkaline solubilization process and evaluate their nutritional quality to evaluate the bioavailability of essential amino acids. Design/methodology/approach: The proximate composition, essential amino acid composition, in vitro digestibility, apparent bioavailability, chemical score of amino acids and SDS-PAGE were determined for the isolated croaker proteins. Findings: The isolated protein showed a high level of protein 92.21 percent and low amount of lipids 0.57 percent. The protein is rich in lysine and leucine, 108.73 and 96.75 mg/g protein, respectively. The protein isolate had high digestibility, 94.32 percent, which indicates proper utilization of this protein source, while the tryptophan had lower bioavailability (12.58 mg amino acid/mg protein). The high chemical scores were found for the amino acids lysine, methionine+cysteine (6.79 and 5.14). SDS-PAGE of proteins extracted showed appearance of the heavy chain of myosin (220 kDa), actin (50 kDa) and other fractions, with molecular weight between 20 and 50 kDa, such as troponin I, C and T. Originality/value: The products obtained from croaker muscle can be incorporated as a high value supplements in human diets. The isolated protein exhibited a high content of essential amino acids and digestibility, indicating that the protein has a high nutritional quality. © Emerald Group Publishing Limited.
Keywords: Amino acid; Croaker; In vitro digestibility; Protein; Solubilization